VPHGs for WEAVE: design, manufacturing and characterisation - Bianco, A; Pariani, G; Aliverti, M; Zanutta, A; Arns, J; Pragt, J; Stuik, R; Middleton, K; Tosh, I; Dalton, G; Trager, S; Abrams, DC; et al. (Society of Photo-optical Instrumentation Engineers, 2018)
WEAVE is the next-generation optical spectroscopy facility for the William Herschel Telescope (WHT). It shows two channels (blue and red) and two working modes, a low-resolution (R=3,000-7,500) and a high-resolution (R=13,000- 25,000). The dispersing elements of the spectrograph are Volume Phase Holographic Gratings (VPHGs), two for the lower resolution mode and three for the higher resolution mode. Such gratings have a large size (clear aperture > 190 mm) and they are characterized by some key features, i.e. diffraction efficiency, wavefront error and dispersion that affect the final performances of the spectrograph. The VPHGs have been produced by KOSI based on the WEAVE design. After that, the VPHGs have been characterized, showing interesting results in terms of diffraction efficiency that reached peak values of 90%. As for the wavefront distortion, which is one of the critical aspect in VPHG technology, a different behavior between medium and high resolution elements was found. A larger wavefront distortion have been measured in the high resolution elements, because of the higher aspect ratio. A polishing process on the assembled VPHGs has been performed in order to reduce the wavefront distortion. Here, the results are presented and the specific issues discussed.